Characterization of extracellular protease produced by Bacillus tequilensis ON1 - Nguyễn, Quang Lịch; Nguyễn, Đức Huy; Trịnh, Thị Phương Thảo; Lê, Thị Kim Thoa; Lê, Công Tuấn (Hue University Journal of Science: Natural Science, 2022)
A bacterial strain with casein hydrolytic activity was isolated from shrimp waste sludge from a culture pond at Phong Dien, Thua Thien Hue. Molecular identification using 16S rRNA nucleotide sequence shows a high similarity to Bacillus tequilensis on the NCBI database. Hence, the isolate was named B. tequilensis ON1. Extracellular protease activity value is 192,42 U·mL–1 after 24 h culture. Zymogram SDS-PAGE electrophoresis shows that the major extracellular protease has a molecular weight of 130 kDa. The enzyme exhibits maximal activity at 50 °C and pH 8. Protease activity increases in the presence of Ca2+ and Mg2+ ions, while Mn2+ inhibits protease activity. The protease activity was more active and stable in hydrophobic organic solvents.